The development of a disruptive innovation response framework within the South African insurance context: adapt, regenerate, transcend (Art) - Amos, Shereen (Graduate School of Business (GSB), 2020)
Companies, nations, governments and multilateral organisations are each in their context recognising that 20th-century approaches to innovation and competitiveness are no longer relevant or effective – with whole industries and economies challenged by the fastmoving and disruptive forces of 21st-century technologies that enable unprecedented innovative capability. The rate and scale of change and disruption calls for innovation thinking more suited to a world highly connected and networked and rapidly redefined by global digital architecture and alternative forms of value exchange, value creation and capture enabled through networks, platforms, and innovation ecosystems. For a mature industry to navigate potential disruption on this scale and possibly direct disruptive innovation of its own, will require a dramatic departure from innovation and business as usual. Christensen (1997) posits that disruptive innovation is the only way for incumbents to maintain market leadership and secure future growth. So how should mature firms respond to disruption, and which strategies are effective to become disruptive too? I undertake a grounded theory study into how specifically, the insurance industry (life and health), navigates disruptive influence and plans to become disruptive too. My analysis of the literature and the research findings has led to the development of an Adapt, Regenerate, Transcend response strategy framework, the ART framework, which describes these three broad response strategies and a further set of sub-strategies, that answer the question of how firms respond to disruptive influence and become disruptive too. The ART framework is my contribution to the work on disruptive innovation response strategies. The framework shows how incumbents can apply one or more of these three broad strategies to suit their objectives. The adapt response strategy, a short-term, defensive or opportunistic strategy, aims to extend lifecycles and fend off disruptive challenges. The regenerate response strategy is an expansive, increasingly inclusive, and transformative hybrid strategy that seeks to extend lifecycles and pursue new growth opportunities that might transform the core business over time to become disruptive too. The transcend response strategy is an original and disruptive strategy where the lead firm partners to reframe and reinvent an industry through a collectively directed value proposition that creates an entirely new playing field. Using the ART framework, I also show how disruptive innovation is an inclusive innovation strategy and how the framework applies to and is of use in the context of inclusive and sustainable innovation. In doing so, a new meta-innovation concept of generative innovation emerges, which the framework begins to describe broadly and which I propose as an area of future research.